Resposta da fauna de insetos associados à serrapilheira em relação a diferentes estágios de recuperação no Cerrado - THALITA MORAES MIRANDA RIBEIRO DE SOUZA (2023)
The study tested the effect of the recovery time of an area on edaphic insect composition and evaluated the composition and restoration of leaf litter insect communities in areas with different levels of disturbance. The study was conducted on a private property in the municipality of Ribas do Rio Pardo, Mato Grosso do Sul State. The property has areas in three different successional stages of natural recovery of the Cerrado: (1) pasture areas with intense and moderate use; (2) areas that were previously used for pasture but, due to lack of use, recovered naturally and have been without human intervention for approximately 15 years; (3) preserved areas composed of two large remnants, one of which is a Private Natural Heritage Reserve (RPPN). The single collection was carried out during rainy season, where 10 plots (with four pitfall traps per plot) were delimited per area. The insects were identified to the family level and for each sampled plot, the individuals' biomass was calculated. To detect differences between families and their respective biomass, a non parametric Kruskal-Wallis test was performed. For analysis of similarities in the composition of taxa, the ANOSIM test was performed. 67 families of adult insects and 7 subfamilies of ants were collected, with Formicinae being the group with the highest biomass. The study showed that the area with the greatest taxonomic and functional group diversity was the intermediate regeneration area, which can be explained by the intermediate disturbance theory. Therefore, it is concluded that the heterogeneity of an environment is important for the diversity of species and functional groups, and we emphasize the importance of future studies in the area.